Women in art - Ignotofsky, Rachel, 1989- (New York Ten Speed press, 2019)
"New York Times bestseller Rachel Ignotofsky's Women in Art comes to the youngest readers in board format!"--
Ages 0-3
Grades K-1
Keywords: Women artists -- Biography -- Juvenile literature